2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037094
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical procedure to assess sleep restriction on motor control and learning

Abstract: The analysis of sleep quality during long periods and its impact on motor control and learning performance are crucial aspects for human health. The aim of this study is to analyze effects of chronic sleep restriction on motor performance. It is intended to establish motor control indicators in sleep quality analysis. A wearable actigraphy that records accelerometry, ambient light, and body temperature was used to monitor the sleep habits of 12 healthy subjects for two weeks before performing motor control and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…Pelos resultados, nota-se que a frequência natural (ƒ) se deu em torno de 0,37 Hz para todos os casos de maiores oscilações, o que é bem próximo ao valor teórico. 114,116,117,118,119,120,125,126,127 N Nióbio 114,115,116,117,118,121,123,126 , 104, 116, 117, 118, 119, 120, 121, 125, 126 T Temperatura 3,4,5,7,9,10,11,14,17,19,48,49,50,51,52,53,54,55,56,67,68,69,70,71,73,75,115 Termorretificação 1,2,4,5,7,8 Teste controle 81…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Pelos resultados, nota-se que a frequência natural (ƒ) se deu em torno de 0,37 Hz para todos os casos de maiores oscilações, o que é bem próximo ao valor teórico. 114,116,117,118,119,120,125,126,127 N Nióbio 114,115,116,117,118,121,123,126 , 104, 116, 117, 118, 119, 120, 121, 125, 126 T Temperatura 3,4,5,7,9,10,11,14,17,19,48,49,50,51,52,53,54,55,56,67,68,69,70,71,73,75,115 Termorretificação 1,2,4,5,7,8 Teste controle 81…”
Section: Resultsunclassified
“…Para isso, a raiz do valor quadrático médio das curvas experimentais e teóricas foi calculado, uma razão entre estes foi efetuada e então multiplicada na curva experimental.Após isto, uma Transformada Rápida de Fourier (FFT -Fast Fourier Transform) foi aplicada em ambas as curvas para chegar ao domínio da frequência do sistema.Para o caso com o flash, o valor obtido foi ɑ 0 =6,66 m/s 2 . Seguindo os mesmos passos, chega-se na Equação(8), que demonstra o deslocamento para este caso.…”
unclassified
“…Previous studies found that poor SQ is associated with impaired motor function [42]. A biomechanical analysis found that SQ can affect motor performance [43]. In neurologic populations, poor SQ negatively affects motor skills acquisition [44] and motor learning [45], which impairs motor recovery.…”
Section: Discussionmentioning
confidence: 98%
“…Interface háptica 81,82,83,84,85,87,88,89,97 114,116,117,118,119,120,125,126,127 N Nióbio 114,115,116,117,118,121,123,126 , 104, 116, 117, 118, 119, 120, 121, 125, 126 T Temperatura 3,4,5,7,9,10,11,14,17,19,48,49,50,51,52,53,54,55,56,67,68,69,70,71,73,75,115 Termorretificação 1,2,4,5,7,8 Teste contr...…”
mentioning
confidence: 99%